Hubungan Psychological Well-Being dengan Prokrastinasi Akademik pada Mahasiswa Tingkat Akhir Program Studi Pendidikan Dokter Universitas Lampung - Rizqi Hidayat; Rasmi Zakiah Oktarlina; Ari Irawan Romulya (Medula, 2026)
The massive academic and clinical burden on final-year medical students is highly prone to triggering stress that leads to increased academic procrastination, a phenomenon that can be mitigated through the optimization of psychological well-being (PWB). This study aims to identify the relationship between PWB and academic procrastination among final-year students of the Medical Education Study Program at the University of Lampung. The research design employed an observational analytic method with a cross-sectional approach. Out of a target population of 146 students from the 2020 cohort, a final sample of 141 respondents was selected using the total sampling technique, while 5 students were excluded due to being academically inactive or declining to participate. Primary data collection relied on validated and reliable Indonesian versions of the Psychological Well-Being Scale (PWBS) and Academic Procrastination Scale (APS), which were subsequently analyzed using the non-parametric Rank Spearman correlation test. The univariate analysis results showed that respondents' PWB levels were dominated by the moderate category with 92 students (65.3%), and procrastination levels were also predominantly moderate with 110 students (78%). Furthermore, the bivariate analysis confirmed a significant but weak negative correlation between psychological well-being and academic task deferral behavior (p=0.01; r=−0.216). This finding demonstrates an inverse trend; the enhancement of students' psychological emotional states is accompanied by a decrease in procrastination intensity. In conclusion, a psychologically healthy mental state is proven to serve as an effective internal protective factor that minimizes academic procrastination behavior among final-year medical students.